An approach to the determinants of financial default of smes in Arequipa - Marco Antonio Llaza Loayza (2019)
This paper examines the determinants of compliance with their claims for a sample of SMEs in Arequipa. All variables which reflect the company’s compliance with financial credits show, with its significance and sign that more SMEs meet their financial obligations within the period established by those who have gotten loans with lower interest rates, they have higher returns on their activities, increased commercial activity and profitability and have a longer life. The paper also provides empirical support for theories that justify microcredit, despite having a different orientation than the conventional credit from commercial banks, basically performs the same rationale that makes lending more expensive for companies with less history, less sales and less profit.